Karakteristik Senyawa Bioaktif dan Profil Sensori Permen Keras Berbasis Tamarillo (Solanum betaceum cav) - Hastuti, Arti; Nurhalimah, Siti; Siti Nurlaela, Raden; Sonia Irli, Sosa (Jurnal Ilmu Pangan dan Hasil Pertanian, 2025)
Hard candy is a solid product made from sugar with or without the addition of sweeteners and other food additives. This study aims to diversify local food processing of hard candy making with the addition of tamarillo juice. The experimental design used in this study was a completely randomized design (CRD) with one factor, namely the amount of tamarillo juice with 4 treatment levels (0%, 10%, 15%, and 20%) with two replications. The chemical characteristics test of tamarillo juice hard candy was carried out including water content, ash content, and reducing sugar. Sensory and hedonic quality characteristic tests Determination of selected products aims to obtain hard candy products with the best treatment which will then be tested for saccharose and antioxidant activity. The addition of tamarillo juice concentration to hard candy affects water content, ash content and reducing sugar in all treatments. The sensory quality of the candy shows a color that tends to orange, sweet and sour taste, hard texture and a distinctive tamarillo aroma. The hedonic test showed that panelists liked the color, sweet taste, aroma and texture. Hard candy with the addition of the selected tamarillo juice concentration, namely the addition of tamarillo juice concentration of 10% with chemical test results of water content of 0.51%, ash content of 0.25% and reducing sugar of 8.90% which was then tested for saccharose and antioxidant activity. The results of the saccharose test were obtained at 64.56% and antioxidant activity was 1.388mg/L which is categorized as weak.